IRRITABILITY IN CHILD AND ADOLESCENT ANXIETY DISORDERS - Stoddard, Joel (BlackWell Publishing Ltd, 2014)
BACKGROUND: Our objective was to compare self- and parent-reported irritability in youths with anxiety disorders, healthy youths, and those with mood disorders characterized by irritability. Irritability is a common but relatively understudied psychiatric symptom in child and adolescent anxiety disorders. In anxious youths, little is known about the severity of irritability, its impact on functioning, or the effect of informant source on reports of irritability. METHODS: We compared parent- and self-report forms of the Affective Reactivity Index (ARI), a validated measure of irritability, in youths ages 8–17 years with no psychopathology (healthy comparison, HC; n = 38), anxiety disorders (ANX; n = 42), bipolar disorder (BD; n = 35), or severe mood dysregulation (SMD; n = 61; a phenotype characterized by chronic, severely impairing irritability). RESULTS: Irritability was significantly higher in ANX than HC youths by both parent and self-report (partial η(2) = 0.24 and 0.22, respectively, P’s < 0.001). Informant effects differed among ANX, BD, and SMD. Overall, parent-reported irritability was higher in BD with comorbid anxiety disorders and SMD with or without comorbid anxiety disorders than ANX (P’s < 0.007), but self-reported irritability was not significantly different among the three patient groups. DISCUSSION: By both parent and self-report, youths with anxiety disorders exhibit significantly more irritability and associated impairment than healthy subjects. Self-reported irritability in youths with anxiety disorders is comparable to that observed in youths with severe mood disorders, although parental reports of irritability differ among the disorders. Future research should examine the pathophysiology of anxiety-associated irritability, as well as its prognostic and treatment implications.